The structurally functional organization of cells in respiratory waysto norm and at a pathology - I. V. Sukhodolo; Ye. A. Gereng (Бюллетень сибирской медицины, 2008)
The term the APUD-system represents an abbreviation of four English words: Amine Precursore Uptake and Decarboxylation, these cells designating the basic property: ability to absorb predecessors entered from the outside biogenic amine to subject them decarboxylation with the subsequent formation biogenic amine and hormones. Biologically active substances which are produced by cells APUD-systems, are responsible for formation of conditioned reflexes, stages of memory and a dream, for formation of painful and emotional sensations.